Soil and Water Physicochemistry in The Hiding Habitat of Mangrove Crabs (Scylla serrata) in the Mangrove Ecosystem on the Coast of Lampu Satu, Merauke Regency, South Papua Province - Masiyah, Siti; Lutfi, Mohammad Ali; Suriani, Wa Ode (Agrikan Jurnal Agribisnis Perikanan, 2023)
Research with the aim of knowing the physicochemistry of soil and water where mangrove crabs hide in the mangrove ecosystem at Lampu Beach, Merauke District, Merauke Regency. The research was conducted for 3 months using the purposive sampling technique survey method. Soil analysis, soil COD, soil BOD, was conducted at Surakarta state university. The results of the fishing carried out for 1 month obtained the number of crabs 15 with details of 9 crabs from station 1 and 6 crabs from station II. Processed the depth of the Hideout 12 – 62cm. with a surface circumference of 5 – 19cm. The results of analysis of soil fractions with three times of testing obtained dusty loam and sandy loam types. The results of the physical and chemical analysis of the soil and water on the substrate obtained a water temperature of 27 - 290C, a water salinity of 0.5 - 1 ppt, a water pH of 6.1 - 7.2 at station 1 and 6.6 - 7.2 at station II. Soil pH at station I was 6.2 – 2.4 mg/l at station II 6.3 – 6.8 mg/l. Soil BOD values were 2.4 – 4.1 mg/l at station I and at station II, 2.4 – 6.1mg/l. COD values at station 1. 4.98 – 6.11mg/l at station II value The COD obtained is 4.71 – 6.8 mg/l. Both soil texture and physico-chemistry of the substrate and water are suitable for the survival of mangrove crabs.